Evangélikus diákok Wittenbergben - Fabiny, Tamás (Gerundium, 2017)
Lutheran students in Wittenberg. The essay presents a short overview of Lutheran students from Hungary in Reformation-time Wittenberg. More than a thousand pastors-to-be spent several semesters in Germany, the Lutheran orientation of which influenced their further career. Scholarly research has revealed an impressive amount of details regarding this multifaceted group of students, Mátyás Dévai Bíró among the most well-known. Luther’s Table Talks include a variety of remarks related to Hungarian students. Dévai Bíró also appears in the 10th, closing episode of the Luther animation series being produced for 2017. In the last section, the author shortly presents three ex-Wittenberg students whose heritage lies in hymn writing: Besides Dévai, the works of András Farkas and András Batizi. Tihe philological and theological input the Wittenberg students produced for the Evangelical Lutheran Church in Hungary was accompanied by intensive international networking exemplary for us today.